The IκB Kinases Restrict Human Cytomegalovirus Infection - Goodwin, Christopher M. (J Virol, 2019)
Human cytomegalovirus (HCMV) is a ubiquitous herpesvirus that causes disease in immunosuppressed populations. HCMV has a complex relationship with innate immune signaling pathways. Specifically, HCMV has been found to block some aspects of inflammatory signaling while benefiting from others. Through analysis of knockout cell lines targeting the NF-κB regulatory kinases IκB kinase α (IKKα) and IKKβ, we find that the IKKs are host restriction factors that contribute to cytokine-mediated resistance to viral infection, limit the initiation of HCMV infection, and attenuate viral cell-to-cell spread. The HCMV U(L)26 protein is a viral immune modulator important for HCMV infection that has been shown to inhibit host cell NF-κB signaling, yet it has remained unclear how U(L)26-mediated NF-κB modulation contributes to infection. Here, we find that U(L)26 modulation of NF-κB signaling is separable from its contribution to high-titer viral replication. However, we find that IKKβ is required for the induction of cytokine expression associated with ΔU(L)26 infection. Collectively, our data indicate that the IKKs restrict infection but HCMV targets their signaling to modulate the cellular inflammatory environment. IMPORTANCE Innate immune signaling is a critical defense against viral infection and represents a central host-virus interaction that frequently determines the outcomes of infections. NF-κB signaling is an essential component of innate immunity that is extensively modulated by HCMV, a significant cause of morbidity in neonates and immunosuppressed individuals. However, the roles that various facets of NF-κB signaling play during HCMV infection have remained elusive. We find that the two major regulatory kinases in this pathway, IKKα and IKKβ, limit the initiation of infection, viral replication, and cell-to-cell spread. In addition, our results indicate that these kinases contribute differently to the host cell response to infection in the absence of a virally encoded NF-κB inhibitor, U(L)26. Given the importance of NF-κB in viral infection, elucidating the contributions of various NF-κB constituents to infection is an essential first step toward the possibility of targeting this pathway therapeutically.